Sexual violence among females who reports to Sanglah Hospital from January 2014 until October 2015 - Tharsini Raja; Ida Bagus Putu Alit (Intisari Sains Medis, 2018)
Background: Sexual violence usually involving sexual intercourse or other forms of sexual penetration perpetrated against a person without that person's consent. Available data suggest that in some countries nearly one in four women may experience sexual violence by an intimate partner, and up to one-third of adolescent girls report their first sexual experience as being forced.Methods: This descriptive cross-sectional study was conducted at Forensic Department of Sanglah General Hospital, Denpasar, Bali between July 2015 – November 2015.  A total of 44 women who came to Sanglah General Hospital with complain of sexual violence between January 2014 – October 2015 were involved in the study.Results: The highest incidence of sexual violence in women who reports to Sanglah General Hospital are within the age range of 20-29 years old (36%). The majority of sexual violence in this study were commited by someone known by the victim, namely victim’s boyfriend (41%), followed by their husband (18%), ex-husband (5%) and second husband (5%).  Most of the victims did not resist during the sexual violence (80%) and had history of previous sexual relationship (86%).Conclusion: Signs of vaginal penetration were found in all of the victims. Most of the victims reported painful intercourse as a result of the violence, and presented with stable emotional state.